From Borrowing to Shared Narratives: Reassessing Abraham Geiger's Hypothesis in the Light of Late Antique Qur'anic Intertextuality - Moh. Nor Ichwan (International Journal of Religious and Interdisciplinary Studies, 2025)
This study critically reassesses Abraham Geiger's 19th-century hypothesis, which posited that the Qur'an largely borrows from rabbinic texts, through the lens of contemporary Qur'anic intertextuality and late antique studies. Drawing on Geiger's Judaism and Islam as its primary unit of analysis, alongside the Qur'anic text and early rabbinic literature, the article seeks to reposition his influential but methodologically flawed thesis within modern scholarly frameworks. Employing a historical-hermeneutic and intertextual methodology, the analysis moves beyond Geiger's reductionist "borrowing” paradigm. Key findings reveal that while Geiger's work retains heuristic value in identifying narrative parallels, it suffers from critical weaknesses: an overreliance on written-text assumptions, Orientalist bias, and a neglect of the oral cultural context of the Hijaz. The study's novelty lies in reconceptualizing these parallels not as evidence of direct dependency, but as manifestations of a dynamic shared narrative network within the late antique religious milieu. In this network, the Qur'an emerges as a creative, dialogical agent that engages, corrects, and innovates upon existing monotheistic traditions. The article contributes to Qur'anic studies by offering a historiographic critique of Orientalist methodology and by proposing a more nuanced, context-sensitive model for understanding early Islamic engagement with Jewish and Christian narratives. It recommends future multidisciplinary research integrating philology, oral anthropology, and socio-political analysis of pre-Islamic Arabia.